Analisis Proyeksi Target Capaian Pajak Daerah Berbasis Potensi Wilayah - Rahmat Maulana; Pandri Ferdias; Agus Lukman Hakim; Zaenal Abidin; Ali Salmande; Miftah Faiz Ali Ramdhani; M Robbi Qawi (Sawala : Jurnal Administrasi Negara, 2023)
This research is to analyze the potential of local taxes and their achievement targets in Serang Regency. The research approach used is quantitative. Data collection techniques with documentation studies using secondary data from various documents from several agencies. The analysis technique used is projection analysis with reference to macroeconomic indicators, the weight prediction of obstacles and opportunities refers to the IFAS-EFAS matrix. The results of the study show that first, the determination of tax potential and targets must be carried out scientifically referring to the juridical basis and economic indicators which refer to both national and regional economic growth and the weight of the obstacles faced in tax management based on expert judgment.